Marginal Microleakage of Low-shrinkage Composite Silorane in Primary Teeth: An In Vitro Study - Hamid Reza Poureslami; Fatemeh Sajadi; Maryam Sharifi; Shahram Farzin Ebrahimi (Journal of Dental Research, Dental Clinics, Dental Prospects, 2012)
Background and aims. Despite the increasing demand for adhesive restorations in pediatric dentistry, polymerization shrinkage and subsequent marginal microleakage remains a problem. The aim of this study was to evaluate of the sealing ability of novel low-shrinkage composite silorane in class V cavity of primary canines in comparison with three types of composite resin. Materials and methods. Ninety-one non-carious extracted primary canines were randomly divided in six groups (n=15). Standard class V cavities were prepared on the buccal surface of each tooth that the occlusal margin was in the enamel and the cervical margin extending 1 mm below the cemento-enamel junction. The preparations were restored with the different composite materials in normal consistency with application the bonding in six groups (Filtek silorane; etch + Filtek Silorane; Z250; Filtek supreme; els saremco; Aelite LS). Teeth were then exposed to thermal cycles (1000 cycles, 5°C and 55°C), sealed and immersed in a 0.5% basic fuchsine for 24 hours, and finally sectioned. Buccolingual and marginal leakage was assessed with dye penetration. Results. The best seal were obtained with etch + Filtek Silorane (P < 0.05) and the weakest seal with Z250 composite restorations (P > 0.05). Except for etch + silorane, there was no significant differences in sealing ability (P > 0.05), and in the microleakage degree at the cementum and enamel margins (P > 0.05) between the groups. Conclusion. According to the results, low-shrinkage silorane composite restorations with etching the cavity provide the highest seal in primary teeth.